AN ANALYSIS OF STUDENTS’ VOCABULARY ABILITY IN FINDING VERB THROUGH SONG LYRICS IN SMP MARISI MEDAN - Mian Ronauli Manurung; Irvi Marca A Munte; Khairun Nisa; Sri Ninta Tarigan (STKIP PGRI Jombang, 2020)
This research was aimed to find out the students’ vocabulary ability in finding verb through song lyrics. And this study has done in SMP MARISI Medan. Speaking is one of the language skills in English. That’s why mastery vocabulary is needed by every people. Vocabulary is a set of similar words within a person’s language. A vocabulary, usually developed with age, serves as as useful and fundamental tool for communication and acquiring knowledge. Teaching vocabulary through song is not only sing or reading lyric of song and fun so that is make the students passive but also process of teaching these vocabulary to be applied in activities in a form of communication.The result of analysis showed that finding verb through song lyrics answered by students’. The students’ who got excellent is 18 (60%), the students’ who got good is 10 (33,3%) . so after the writer got there are score, the writer concluded that students’ who got excellent and good categorized able. The students’ who got categorized Bad2 (6,6%) students’. So, after the writer got there are score, the writer conclude that students’ who got enough and bad categorized unable in finding verb. The researcher hopes that the students’ should be active in learning especially on vocabulary because vocabulary is one of important skills in learning English. The students’ must develop their vocabulary so they can speak well in English. Moreover, the students’ may get more knowledge to improve their vocabulary in English.